Ophthalmic manifestations and management considerations for emerging chemical threats - Menke, Bryant A.; Ryu, Christine; Justin, Grant A.; Chundury, Rao V.; Hayek, Brent R.; Debiec, Matthew R.; Yeh, Steven (Frontiers in Toxicology, 2023)
Chemical agents have been utilized for centuries in warfare and pose a health threat to civilians and military personnel during armed conflict. Despite treaties and regulations against their use, chemical agent exposure remains a threat and measures to understand their effects and countermeasures for systemic and organ-specific health are needed. Many of these agents have ocular complications, both acute and chronic. This mini-review focuses on key chemical agents including vesicants (mustards, lewisite), nerve agents (sarin, VX), knockdown gasses (hydrogen cyanide), and caustics (hydrofluoric acid). Their ophthalmic manifestations and appropriate treatment are emphasized. Acute interventions include removal of the source and meticulous decontamination, as well as normalization of pH to 7.2-7.4 if alteration of the ocular pH is observed. Besides vigorous lavage, acute therapies may include topical corticosteroids and non-steroid anti-inflammatory therapies.Appropriate personal protective equipment (PPE) and strict donning and doffing protocols to avoid health care provider exposure are also paramount in the acute setting. For more severe disease, corneal transplantation, amniotic membrane graft, and limbal stem cell transplantation may be needed. Orbital surgery may be required in patients in whom cicatricial changes of the ocular surface have developed, leading to eyelid malposition. Multidisciplinary care teams are often required to handle the full spectrum of findings and consequences associated with emerging chemical threats.